Effect of the COVID-19 pandemic on potential health emergencies in paediatric patients: a retrospective cohort study - Krzysztof Marek Mitura; Daniel Celiński; Jadwiga Snarska; Sławomir Dariusz Szajda (Frontiers Media S.A., 2024)
The COVID-19 pandemic compromised the principles underlying the functioning of public health, which is understood as the prevention of diseases and care for the health of entire communities. During the pandemic period, the efforts of the health system focused on patients with suspected infection and those infected with the SARS-CoV-2 virus, which led to changes in the provision of health services and the characteristics of patients receiving medical services at the pre-hospital stage. The objective of this study was to investigate the effects of the COVID-19 pandemic on potential health emergencies in paediatric patients based on the International Statistical Classification of Diseases and Related Health Problems (ICD-10). The data used in the study were derived from interventions carried out by Emergency Medical Teams (EMT) in central and eastern Poland, involving patients who were under 18 years of age (n = 12,619). The data were collected from 1 January 2017 to 31 December 2022. The study used descriptive statistics, the Mann-Whitney U Test, and the Chi-square test. The study reveals that fewer paediatric patients (5.28%) were provided medical services by EMTs during the COVID-19 pandemic compared to the pre-pandemic period (5.86%). There was a decrease in the number of injuries in paediatric patients (from 42.0 to 32.7%; p < 0.001), and more patients were left at the location from which the call was made (18.9 vs. 23.9%; p < 0.001). Moreover, during the pandemic, as compared to the pre-pandemic period, there was an increase in the number of cases of pre-hospital assistance provided to paediatric patients with fever, irrespective of gender, area (village, city) or patient age. During the pandemic, paediatric patients consumed alcohol more frequently. The age of patients who were provided with assistance by EMTs decreased (median of 10.0 vs. 9.0; p < 0.001). The COVID-19 pandemic brought about changes in the prevalence of potential health emergencies in children. The incidence of injuries decreased, while the number of interventions due to fever and alcohol consumption increased. There was a reduction in the number of patients transported to the hospital. In addition, the age of patients who received medical assistance decreased. The study shows health problems that were faced by paediatric patients during the COVID-19 pandemic and, therefore, can be helpful in preparing the healthcare system for emergency situations.